2017
DOI: 10.1113/ep086585
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular response to the cold pressor test – the critical role of carbon dioxide

Abstract: What is the central question of this study? What is the role of carbon dioxide in the cerebral blood flow (CBF) response to the cold pressor test (CPT)? What is the main finding and its importance? The CBF response was elevated during the isocapnic (controlled CO ) CPT in the middle cerebral artery and the internal carotid artery compared with the poikilocapnic (uncontrolled CO ) CPT, owing to ventilation-associated reductions in end-tidal CO . Furthermore, the common carotid artery vasodilated to a greater ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
(186 reference statements)
2
16
0
Order By: Relevance
“…PnormalETCO2 controlled at +1 mmHg baseline) MCA v mean increased during CPT (Protocol 2). Such findings agree with those of Tymko, Kerstens, Wildfong, and Ainslie (2017) and highlight the importance of nociceptor‐mediated alterations in ventilation, and thus PnormalETCO2, on blunting the cerebral perfusion response to the CPT. A striking example of the balance between the effects of ventilation, and thus PnormalETCO2, on cerebral perfusion in the cold has been provided by Datta and Tipton (2006).…”
Section: Discussionsupporting
confidence: 90%
“…PnormalETCO2 controlled at +1 mmHg baseline) MCA v mean increased during CPT (Protocol 2). Such findings agree with those of Tymko, Kerstens, Wildfong, and Ainslie (2017) and highlight the importance of nociceptor‐mediated alterations in ventilation, and thus PnormalETCO2, on blunting the cerebral perfusion response to the CPT. A striking example of the balance between the effects of ventilation, and thus PnormalETCO2, on cerebral perfusion in the cold has been provided by Datta and Tipton (2006).…”
Section: Discussionsupporting
confidence: 90%
“…We controlled for both P ET ,CO2 and P ET ,O2 during the CPT protocol in order to remove the influence of arterial blood gases on changes in cerebral blood flow (Sato et al., ; Willie et al., ). A recent study performed by our research group demonstrated that during a 0–1°C, 3 min CPT, V̇E was elevated in both males and females, resulting in a reduction in P ET ,CO2 and the diameter response of the CCA (Tymko et al., ). Unfortunately, we were unsuccessful at maintaining isocapnia throughout the entire CPT, because P ET ,CO2 was reduced at CPT2 compared with baseline values; however, the observed reduction was on average <1 mmHg, and importantly, no interaction effect was present between males and females.…”
Section: Discussionmentioning
confidence: 95%
“…Two female participants were excluded from data analyses owing to failure to complete the experimental protocol. The data collected and analysed in the present study includes data from 15 participants (five females) from a previous publication (Tymko et al., ). To extend these findings and in order to compare the sex‐specific response to the CPT adequately, five additional age‐matched female participants were recruited; therefore, the present study was designed to answer this a priori research question.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations